Economic Assistance as a Form of Non-Penal Policy in Countering Terrorism for Ex-Prisoners in Indonesia - Masyhar, Ali; Murtadho, Ali; Aisy, Rohadhatul; Abu, Roziya (Journal of Law and Legal Reform, 2024)
This study highlights the critical role of economic assistance as a non-penal policy in countering terrorism among ex-prisoners in Indonesia. Economic stability emerges as a significant factor in mitigating criminal behavior, particularly terrorism, by addressing the economic roots of radical ideologies. Traditional counterterrorism measures in Indonesia have predominantly focused on punitive approaches, targeting individuals who have committed terrorism offenses through formulation, judicial application, and executive enforcement of penal policies. However, there is an increasing recognition of the limitations of solely punitive measures in preventing recidivism and addressing the broader socio-economic factors that contribute to radicalization. The findings underscore the efficacy of economic interventions in disrupting the cycle of terrorism by providing viable alternatives to individuals vulnerable to radical ideologies due to economic hardships. By offering economic assistance, such as vocational training, job placement programs, and financial support, governments can empower ex-prisoners to reintegrate into society positively. This approach not only enhances the economic stability of former offenders but also reduces their susceptibility to re-engaging in terrorist activities. Moreover, integrating economic welfare assistance into broader counterterrorism strategies promotes a holistic approach that complements punitive measures with preventive measures. It acknowledges the need for synergy between punitive and non-penal policies to effectively combat terrorism. Such integrated strategies are essential for long-term success in reducing terrorism by addressing its socio-economic underpinnings and fostering sustainable peace and stability. In conclusion, this study advocates for the prioritization and implementation of economic assistance programs tailored for ex-prisoners in Indonesia as a crucial component of comprehensive counterterrorism efforts. By investing in economic stability, governments can effectively undermine the appeal of radical ideologies and contribute to lasting security and societal resilience.